Leaf spots of Calibrachoa caused by Nogrospora oryzae - Borrelli, Nicolás Pablo; Stancanelli, Santiago; Papone, Mirta Leonor; Moreno, María Virginia; Stenglein, Sebastian; Wright, Eduardo R.; Hagiwara, Juan Carlos; Rivera, Marta Carolina (Sociedade Brasileira de Floricultura e Plantas Ornamentais, 2021)
Calibrachoa hybrida (calibrachoa, million bells) is a flowering ornamental with increasing importance due to the existence of many successful cultivars for growing indoors in containers and planting in the garden and landscape. The outstanding characteristic is a profuse flowering and intense colour. In October 2019, a fungal isolate was obtained from basal calibrachoa leaves with irregular brown leaf spots, in plants cultivated in Buenos Aires, Argentina. The aim of the present study was to identify the cause of the disease in this ornamental genus, to expand knowledge about prevalent pathologies. The isolate was identified using morphological and molecular markers, and the pathogenicity tests were fulfilled. This paper reports that Nigrospora oryzae is pathogenic to calibrachoa, which seems to be the first record of this leaf spot disease in the world.